1993
DOI: 10.1093/clinchem/39.3.533
|View full text |Cite
|
Sign up to set email alerts
|

How and how long to store urine samples before albumin radioimmunoassay: a practical response

Abstract: We used three study protocols to check the dependence of albumin stability, measured by an RIA, on different temperatures, durations, and materials (i.e., assay tubes) of urine storage. Albumin values obtained for samples stored in three types of assay tubes (glass, polystyrene, and polypropylene) throughout the 2 months of the first (prospective) protocol were superimposable. The 24-h storage of six urine samples at room temperature or at 4 degrees C, as well as 72-h storage at 4 degrees C, did not affect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 12 publications
0
6
1
1
Order By: Relevance
“…We found that delaying the laboratory analysis of samples by 24–48 h (stored at 4 °C) did not affect the results; however, delaying the analysis by 3–9 months (stored at −80 °C) resulted in a systematic overestimation of ACR of approximately 8 %. The latter observation contrasts to previous studies which found either no change in ACR [ 23 25 ] or a 10 % decrease after long-term storage of frozen samples [ 26 28 ]. While a detailed investigation into the effects of sample processing on ACR measurement was beyond the scope of this study, others have shown that laboratory assay parameters (which are not standardized across laboratories) can affect ACR measurement.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that delaying the laboratory analysis of samples by 24–48 h (stored at 4 °C) did not affect the results; however, delaying the analysis by 3–9 months (stored at −80 °C) resulted in a systematic overestimation of ACR of approximately 8 %. The latter observation contrasts to previous studies which found either no change in ACR [ 23 25 ] or a 10 % decrease after long-term storage of frozen samples [ 26 28 ]. While a detailed investigation into the effects of sample processing on ACR measurement was beyond the scope of this study, others have shown that laboratory assay parameters (which are not standardized across laboratories) can affect ACR measurement.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have measured the stability of albumin in frozen samples, with mixed results. Numerous studies have found negligible effect of freezing on urinary albumin concentration 13 while others have found considerable albumin losses. 49 The use of stored samples for albuminuria research has been criticized due to the potential for long-term degradation of albumin in stored urine.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages are increased control on logistics and prevention of analytical day-to-day variation and drift. Although some studies found no effect of frozen storage on UAC [6][7][8], others found erroneously low values, in particular if storage was for 6 months or longer [9][10][11][12]. Importantly, the decline in UAC during frozen storage has been reported to vary greatly between samples, making the decline for an individual sample very unpredictable [13,16].…”
Section: Introductionmentioning
confidence: 99%